Prevalência de doença por citomegalovírus em pacientes transplantados renais com suspeita clínica desse diagnóstico - Santos, Sanmya Danielle Rodrigues dos [UNIFESP] (2017)
Objectives - Cytomegalovirus (CMV) disease is one of the most frequent complications after kidney transplantation. Our objectives were to determine the prevalence of CMV disease among kidney transplant patients in the ICU who had a clinical suspicion of this complication, to identify its predisposing factors, and to analyze whether CMV disease impacts on the clinical evolution of these patients. Methods - In this retrospective observational study, we included all kidney transplant patients over 18 years of age, hospitalized for any reason in an intensive care unit (ICU), with at least one sampling of antigenemia or polymerase chain reaction (PCR) for CMV during the ICU stay. Patients who had graft loss more than 6 months ago, or those diagnosed with CMV at admission were excluded. CMV disease was defined as positive antigenemia at any level or a PCR above 500 log in the presence of symptoms. Results – We included 99 patients with a mean age of 53.4 ± 12.8 years being 71.6% male. All patients were using immunosuppression, but only 26 (26.3%) had received pulse therapy in the last six months, 32 (32.2%) had received thymoglobulin sometime in the past and 18 (18,2%) received thymoglobulin in the last year. Respiratory symptoms (51%), non-specific clinical worsening (20%) or gastrointestinal symptoms (14%) were the main reasons for CMV laboratory sampling. CMV disease was diagnosed in 39 patients (39.4%), of whom 20 (51.2%) had positive antigenemia in the first sampling, four (10.3%) had positive antigenemia in the second sampling, and 15 (38.5% %) were diagnosed by PCR. Time since transplantation was shorter in those diagnosed with CMV disease than in those without this diagnosis (6.5 months and 31.2 months, p = 0.001). Both the use of pulse therapy in the last six months (41% and 16,9%, p = 0.008) as the previous use of thymoglobulin in the prior 12 months before admission (35.9% and 6.8%, p <0.001) were more frequent among those with CMV disease. In the logistic regression model, only the time since transplantation less than 6 months [OR 4.755 (95% CI -1.497 to 12.785, p = 0.007]) and thymoglobulin use in the last 12 months [OR 4.855 (CI 95% -1.334 to 17.530), p = 0.016] were associated with a higher frequency of CMV disease. There was no difference in the clinical evolution between patients with and without CMV disease. Conclusion: The prevalence of CMV disease in kidney transplant patients admitted to the ICU, in whom there is a clinical suspicion of this disease, is high. The predisposing factors independently associated with increased risk of CMV disease in this population were time since transplantation less than six months and thymoglobulin use in the prior year before admission. Patients with CMV disease did not have worse clinical outcomes as compared with patients without CMV.